Immunohistochemical Expression Levels of Epidermal Growth Factor Receptor, Cyclooxygenase-2, and Ki-67 in Canine Cutaneous Squamous Cell Carcinomas - João Miguel Luís; Rita Files; Cláudia Cardoso; José Pimenta; Gabriela Maia; Filipe Silva; Felisbina L. Queiroga; Justina Prada; Isabel Pires (Current Issues in Molecular Biology, 2024)
Squamous cell carcinoma (SCC) stands as the second most prevalent skin cancer in dogs, primarily attributed to UV radiation exposure. Affected areas typically include regions with sparse hair and pale or depigmented skin. The significance of spontaneous canine cutaneous SCC as a model for its human counterpart is underscored by its resemblance. This study assesses the expression of key markers—Epidermal Growth Factor Receptor (EGFR), Cyclooxygenase-2 (Cox-2), and Ki-67—in canine cutaneous SCC. Our objective is to investigate the association between their expression levels and classical clinicopathological parameters, unraveling the intricate relationships among these molecular markers. In our retrospective analysis of 37 cases, EGFR overexpression manifested in 43.2% of cases, while Cox-2 exhibited overexpression in 97.3%. The EGFR, Cox-2 overexpression, and Ki-67 proliferation indices, estimated through immunohistochemistry, displayed a significant association with the histological grade, but only EGFR labeling is associated with the presence of lymphovascular emboli. The Ki-67 labeling index expression exhibited an association with EGFR and Cox-2. These findings propose that EGFR, Cox-2, and Ki-67 hold promise as valuable markers in canine SCC. EGFR, Cox-2, and Ki-67 may serve as indicators of disease progression, offering insights into the malignancy of a lesion. The implications extend to the potential therapeutic targeting of EGFR and Cox-2 in managing canine SCC. Further exploration of these insights is warranted due to their translational relevance and the development of targeted interventions in the context of canine SCC.